Effectiveness of Climate Related Development Finance in Reducing Greenhouse Gas Emissions of Selected African Countries: The Role of Source and Recipient Country Income Levels - Sonono, Obey; Matsvai, Simion; Hosu, Sunday Yiseyon (International Journal of Energy Economics and Policy, 2025)
Despite CRDF allocation opportunities since the Kyoto Protocol in 1997, greenhouse gas emissions in developing countries remain high. Existing evidence on the CRDF-GHG emissions nexus is based on aggregate climate finance without also considering the impact of recipient income levels. This study examined the effectiveness of climate-related development finance in reducing GHG emissions, examine the role of CRDF sources in emissions reduction, and assess the influence of recipient country’s income level. The study used panel data from selected African countries (Botswana, Burkina Faso, Cameron, Ethiopia, Ghana, Kenya, Tanzania, Zambia, and Zimbabwe). Pooled OSL, Random Effects and Fixed Effects were used to analyse the relationship between GHGs emissions as the dependent variable and CRDF, CRDF sources, and recipient income levels as independent variables. The results revealed a significant negative relationship between aggregated CRDF and GHGs emissions. An increase in CRDF leads to investment in mitigatory measures that subsequently decrease GHGs emissions. Furthermore, the study found that CRDF sources have significant heterogeneous effects on developing countries' GHGs emissions where CRDF from Asia result in significant reductions in GHG emissions, while CRDF from Europe increases emissions. The interaction between CRDF and recipient incomes was also found to significantly increase emissions. The study highlights the critical role of CRDF in reducing GHG emissions in the selected African countries. The study recommends a continuous flow of CRDF to developing countries, prioritizing funding sources from Asia complemented by measures to decouple economic growth from emissions thereby further enhancing the effectiveness of CRDF in reducing GHG emissions.